2013
DOI: 10.1155/2013/650358
|View full text |Cite
|
Sign up to set email alerts
|

High Mortality Rate due to False Gid in a Sheep Herd

Abstract: The sheep nasal bot, Oestrus ovis (Diptera: Oestridae), is a cosmopolitan parasite commonly found in sheep and occasionally goats. Rarely a bot will migrate into the sheep brain (false gid). Following the complaint of an animal husbandman about high mortality rate in a sheep herd, the herd was clinically, hematologically, and pathologically examined exactly. Clinical, hematological, and pathological findings were described in the text. Necropsy findings showed heavy infestation with Oestrus ovis larvae. The he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This is expressed as rhinitis with an overproduction of mucus, which promotes the feeding of Oestrus ovis infection of grazing sheep during summer in southern Chile 1 the larvae. Some animals may present a serious infection when the larvae enter the brain through the foramina and they may develop encephalitis, manifesting ataxia, hemiparesis and blindness (Mozaffari et al 2013). Severe injury of the brain tissue may produce a characteristic behavior in sheep known as "gid" which resembles the lesion produced by Coenurus cerebralis, the larval stage of Taenia multiceps (Anwar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is expressed as rhinitis with an overproduction of mucus, which promotes the feeding of Oestrus ovis infection of grazing sheep during summer in southern Chile 1 the larvae. Some animals may present a serious infection when the larvae enter the brain through the foramina and they may develop encephalitis, manifesting ataxia, hemiparesis and blindness (Mozaffari et al 2013). Severe injury of the brain tissue may produce a characteristic behavior in sheep known as "gid" which resembles the lesion produced by Coenurus cerebralis, the larval stage of Taenia multiceps (Anwar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The family Oestridae includes 29 genera grouped into four subfamilies with about 170 species (Scholl et al 2019). Oestrids are obligate parasites in their larval phases, their infestations can increase the likelihood of opportunistic infections and in severe cases can lead to head injury and even death of the host (Mozaffari et al 2013). In this study, we sequenced and analyzed for the first time the complete mitochondrial genome of Oestrus ovis.…”
mentioning
confidence: 99%
“…Oestrosis in small ruminants causes substantial economic losses to sheep and goat producers. 6 , 7 The pathogenic effects cause a reduction in production and serious economic losses, which have been estimated at 1.1–4.6 kg of meat, 200–500 g of wool, and up to 10% of milk per animal. 2 Mozaffari et al 7 also reported a 10% mortality rate of sheep with O. ovis infestation.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 The pathogenic effects cause a reduction in production and serious economic losses, which have been estimated at 1.1–4.6 kg of meat, 200–500 g of wool, and up to 10% of milk per animal. 2 Mozaffari et al 7 also reported a 10% mortality rate of sheep with O. ovis infestation. Besides, oestrosis has public health significance.…”
Section: Introductionmentioning
confidence: 99%